2014
DOI: 10.1177/1557988314552468
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Testosterone and PSA Kinetics in Metastatic Prostate Cancer Patients Treated With Diverse Chemical Castrations

Abstract: To assess total testosterone and prostatic-specific antigen (PSA) kinetics among diverse chemical castrations, advanced-stage prostate cancer patients were randomized into three groups of 20: Group 1, Leuprolide 3.75 mg; Group 2, Leuprolide 7.5 mg; and Group 3, Goserelin 3.6 mg. All groups were treated with monthly application of the respective drugs. The patients' levels of serum total testosterone and PSA were evaluated at two time periods: before the treatment and 3 months after the treatment. Spearman's ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A possible change in the threshold makes it important to find out whether the currently available LHRH agonists differ in effectiveness for obtaining chemical castration at a new, lower threshold. In comparing the potency for lowering serum testosterone levels of different LHRH agonist, a recent study reported mean serum testosterone levels after 3 months of treatment were the lowest with leuprolide 7.5 mg, followed by goserelin 3.7 mg and leuprolide 3.75 mg [19]. Another study found that maintenance of castration was better with triptorelin pamoate 3.75 mg than leuprolide acetate 7.5 mg, but the difference was not statistically significant [7].…”
Section: Discussionmentioning
confidence: 99%
“…A possible change in the threshold makes it important to find out whether the currently available LHRH agonists differ in effectiveness for obtaining chemical castration at a new, lower threshold. In comparing the potency for lowering serum testosterone levels of different LHRH agonist, a recent study reported mean serum testosterone levels after 3 months of treatment were the lowest with leuprolide 7.5 mg, followed by goserelin 3.7 mg and leuprolide 3.75 mg [19]. Another study found that maintenance of castration was better with triptorelin pamoate 3.75 mg than leuprolide acetate 7.5 mg, but the difference was not statistically significant [7].…”
Section: Discussionmentioning
confidence: 99%
“…, 3 months after the first injection, patients with metastatic prostate cancer treated with 1‐month goserelin had significantly lower PSA levels than patients treated with 1‐month leuprorelin 3.75 mg or 1‐month leuprorelin 7.5 mg. However, the reduction in PSA level did not correlate with the reduction in testosterone in this study . In all, 20 patients were included in each group in this study, and therefore, larger scale studies would be needed to determine if goserelin suppressed PSA more effectively than leuprorelin (Level 3).…”
Section: Resultsmentioning
confidence: 88%
“…) . Median testosterone levels were also lower in the higher dose (7.5 mg) leuprorelin group than in the lower dose (3.75 mg) leuprorelin group (Level 2) . However, this difference must be considered with caution as a simultaneous comparison of the three groups did not reach the established significance level.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations